Therapeutic hypothermia and acute brain injury. Issue 1 (January 2020) - Sokhi, Jagdish; Reddy, Ugan
Abstract: Secondary brain injury has devastating effects on morbidity, mortality and good functional outcomes. Neuroprotection is multimodal, with decades of preclinical and small clinical studies showing the benefits of therapeutic hypothermia. The basic scientific principles have merit, yet large randomized controlled trials fail to show a clear benefit. This article will review the basic science the practical aspects of delivering targeted temperature management and evaluate the evidence behind its use for acute brain injuries. With a lack of high-quality evidence for hypothermia, recent consensus statements are shifting the paradigm away from hypothermia to the maintenance of normothermia and prevention of pyrexia.